2016
DOI: 10.1038/cdd.2016.95
|View full text |Cite
|
Sign up to set email alerts
|

The degradation of EZH2 mediated by lncRNA ANCR attenuated the invasion and metastasis of breast cancer

Abstract: EZH2 (the Enhancer of Zeste Homolog 2), as a key epigenetic regulator and EMT inducer, participates in a variety of cancer metastasis. EZH2 stability is regulated by several types of post-translational modifications (PTMs).The long non-coding RNAs (lncRNA) have been implicated to have critical roles in multiple carcinogenesis through a wide range of mechanisms, including modulating the stability of proteins. To date, whether the stability of EZH2 protein is regulated by lncRNAs remains unexplored. Here we repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
224
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 285 publications
(242 citation statements)
references
References 54 publications
(72 reference statements)
8
224
0
1
Order By: Relevance
“…Therefore, by performing RIP assays we demonstrated that PAR5 directly binds EZH2. Moreover, we observed that PAR5 restoration reduced EZH2 protein and H3K27me3 levels in absence of any change of EZH2 mRNA abundance, suggesting that this lncRNA may affect EZH2 stability by a regulatory mechanism already reported for other lncRNAs [32,33]. Consistently with these findings, we found an increased EZH2 expression in ATC tissues and, interestingly, we observed a negative correlation between EZH2 protein and PAR5 RNA levels, strongly supporting the effects of PAR5 on EZH2.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, by performing RIP assays we demonstrated that PAR5 directly binds EZH2. Moreover, we observed that PAR5 restoration reduced EZH2 protein and H3K27me3 levels in absence of any change of EZH2 mRNA abundance, suggesting that this lncRNA may affect EZH2 stability by a regulatory mechanism already reported for other lncRNAs [32,33]. Consistently with these findings, we found an increased EZH2 expression in ATC tissues and, interestingly, we observed a negative correlation between EZH2 protein and PAR5 RNA levels, strongly supporting the effects of PAR5 on EZH2.…”
Section: Discussionsupporting
confidence: 90%
“…Recently, the potential role of DANCR in cancer has been reported in several studies; however, these studies showed that DANCR plays opposite roles depending on the tumour type. In colorectal cancer, hepatocellular carcinoma and prostate cancer, DANCR functions as an oncogene; on the contrary, another report indicated that DANCR functions as a tumour suppressor in breast cancer via degrading the epigenetic tumour regulator EZH2 [13][14][15][16]. This phenomenon may explain the variable expression and biological patterns of DANCR in different cancer types.…”
Section: Discussionmentioning
confidence: 98%
“…* p < 0.05; * * p < 0.01. target genes (Gupta et al, 2010). LncRNA ANCR interacts with EZH2 to promote its phosphorylation that facilitates EZH2 degradation and suppresses breast cancer progression (Li et al, 2017). In this study, we demonstrated that LINC-PINT was an EZH2-binding lncRNA and play an tumorsuppressive role in melanoma progression.…”
Section: Discussionmentioning
confidence: 69%